Magnetic Anisotropy at Nanoscale - Marek W. Gutowski (Journal of Nanotechnology)
Nanoscale objects often behave differently than their “normal-sized” counterparts. Sometimes it is enough to be small in just one direction to exhibit unusual features. One example of such a phenomenon is a very specific in-plane magnetic anisotropy observed sometimes in very thin layers of various materials. Here we recall a peculiar form of the free energy functional nicely describing the experimental findings but completely irrelevant and thus never observed in larger objects.